Inventory Control Analysis di PT. XYZ Menggunakan Metode Probabilistik dengan Kebijakan Backorder dan Lost sales - Zulkarnaen, Rhasya Rurimeilinda; T, Muh Dhiyaurrahman; Mafitasari, Widad Rana; Fauzi, Muchammad (Jurnal Ilmiah Wahana Pendidikan, 2023)
Inventory control is a necessity for the business due to the item's fluctuating demand. A pharmaceutical business that deals with human medicine was where this study was done. The goal of this study is to choose the best inventory control strategy for the organization in order to determine the least quantity of inventory needed while also obtaining the overall cost of inventory. The system and inventory expenses employed by the company were examined from a number of angles during the course of this investigation. Simple probabilistic control, the Q model, and the P model are all components of the researcher's probabilistic inventory technique. The backorder P model offers the best answer when compared to other inventory models, according on the findings of data processing.